2022
DOI: 10.1161/jaha.121.024606
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Properties With the Brain White Matter Hyperintensity in Middle‐Aged Population

Abstract: Background The periventricular white matter is more sensitive to the systemic hemodynamic alterations than the deep white matter because of differences in its vascular structure and systemic circulation relationship. We hypothesize that periventricular white matter hyperintensity (PVWMH) volume shows greater association than deep white matter hyperintensity (DWMH) volume with vascular properties (VPs) reflecting arterial stiffness and cardiovascular remodeling, indicators of the systemic circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“… 21 , 118 , 119 , 120 , 121 , 123 , 124 , 125 , 126 , 127 , 128 , 130 , 131 , 132 , 133 , 134 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 147 , 148 , 150 , 151 , 152 , 153 , 154 , 156 , 157 , 158 , 160 , 161 , 163 , 165 , 166 , 167 , 169 , 171 , 172 , 173 , 176 , 177 , 178 , 179 , 182 , 183 , 185 , 186 …”
Section: Resultsunclassified
“… 21 , 118 , 119 , 120 , 121 , 123 , 124 , 125 , 126 , 127 , 128 , 130 , 131 , 132 , 133 , 134 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 147 , 148 , 150 , 151 , 152 , 153 , 154 , 156 , 157 , 158 , 160 , 161 , 163 , 165 , 166 , 167 , 169 , 171 , 172 , 173 , 176 , 177 , 178 , 179 , 182 , 183 , 185 , 186 …”
Section: Resultsunclassified
“…[169][170][171][172] A few studies have also investigated the relationships between arterial stiffness and the LA subtypes classified on the basis of PVWMH and DWMH, but their results were inconsistent. [173][174][175][176] Two of these studies reported that PWV was statistically significantly associated with both LA subtypes. 173,174 However, two other studies found significantly different associations between arterial stiffness and PVWMH and DWMH 175,176 -in one study, arterial stiffness was associated with PVWMH but not DWMH, 175 whereas in the other, PVWMH had a higher correlation with arterial stiffness than DWMH.…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…[173][174][175][176] Two of these studies reported that PWV was statistically significantly associated with both LA subtypes. 173,174 However, two other studies found significantly different associations between arterial stiffness and PVWMH and DWMH 175,176 -in one study, arterial stiffness was associated with PVWMH but not DWMH, 175 whereas in the other, PVWMH had a higher correlation with arterial stiffness than DWMH. 176 Although the differences between the associations between arterial stiffness and PVWMH versus DWMH need to be clarified, these findings strong-ly suggest that arterial stiffness is associated with LA incidence and severity.…”
Section: Arterial Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, cfPWV assesses an integrated stiffness of different segments of the aorta [19]. Alternatively, carotid arterial stiffness is determined by the changes of the lumen diameter and the arterial pulse pressure at the common carotid artery (CCA) [20], which is a regional arterial stiffness measure close to the brain, thus likely to be more relevant to assess the effects of central arterial stiffening on the brain [12,17,21,22]. In this regard, previous studies have reported that cfPWV and carotid arterial stiffness measured with ultrasonography may reflect different arterial wall properties in healthy adults [23].…”
Section: Introductionmentioning
confidence: 99%